2022
DOI: 10.1590/1678-4162-12471
|View full text |Cite
|
Sign up to set email alerts
|

Hematological and biochemical alterations in female dogs with mammary cancer and inflammatory carcinoma

Abstract: Hematological and biochemical alterations in animals with neoplasms may result from the direct effects of tumor growth or paraneoplastic syndromes. The objective of this study was to evaluate these hematological and biochemical alterations in female dogs with mammary tumors and with inflammatory carcinoma (IC). Blood samples were collected from 43 female dogs divided into three groups according to clinical staging: Group 1 (G1) - animals in initial stage (T1,2,3N0M0, N=17), Group 2 (G2) - animals in advanced s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
3
0
1
Order By: Relevance
“…The prognosis of canine mammary gland carcinomas varies, as described above. In human medicine, hematological changes are considered important determinants of prognosis in patients with neoplasms (10). Similarly, paraneoplastic changes in the blood, including anemia, leukocytosis, erythrocytosis, thrombocytopenia, hyperglobulinemia, hyperviscosity syndrome, and coagulopathy, can be prognostic factors in veterinary medicine (1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prognosis of canine mammary gland carcinomas varies, as described above. In human medicine, hematological changes are considered important determinants of prognosis in patients with neoplasms (10). Similarly, paraneoplastic changes in the blood, including anemia, leukocytosis, erythrocytosis, thrombocytopenia, hyperglobulinemia, hyperviscosity syndrome, and coagulopathy, can be prognostic factors in veterinary medicine (1).…”
Section: Discussionmentioning
confidence: 99%
“…IMC is a clinicopathological entity that is diagnosed based on a combination of clinical features and confirmed by histopathology. To diagnose IMC, physical examination should show erythema, heat, edema, peau d'orange, wheals, and ridging of the skin appearing on more than 1/3 of the breast skin with a medical history of rapid onset (<3 months) and a negative result for bacterial infection (10). Considering the physical examination of inflammatory reactions, such as erythema, heat, and pain around the mammary gland, we presume that the patient has a high possibility of IMC (10).…”
Section: Discussionmentioning
confidence: 99%
“…The highest values were obtained in bitches with a tumor size greater than 5 cm and with tumors in multiple mammary units. Furthermore, Oliveira et al [29] found differences in the concentrations of total serum proteins according to the clinical staging and progression of mammary tumors, with the highest mean value in bitches in the early clinical stage of the disease and the lowest mean value in animals with infl ammatory carcinoma. Among alterations, hypoalbuminemia was a typical fi nding in the aforementioned study, especially in dogs in advanced clinical staging and with infl ammatory carcinoma, refl ecting disease progression and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…No paciente oncológico, esse quadro está relacionado com a indução de danos teciduais pelas células neoplásicas, que dá início a resposta inflamatória aguda, estimula citocinas e quimiocinas a atuarem em todo o organismo(OLIVEIRA et al, 2022).…”
unclassified